AOC reduction by biologically active filtration - Lechevallier, M.; Becker, W.; Schorr, P.; Lee, R. (Revue des sciences de l'eau / Journal of Water Science, 1992)
Biological treatment was examined for production of biologically stable water, increase disinfectant stability, and reduced formation of disinfection by products. Monitoring of assimilable organic carbon (AOC) levels in the effluent of the Swimming River Treatment Plant (SRTP) showed that values >100 µg/L could be related to the occurrence of coliform bacteria in the distribution system. A treatment goal of <100 µg/L was established for biologically active treatment processes. Granular activated carbon (GAC) filters were found to support a larger bacterial population, and thus, provide better biological removal of AOC and total organic carton (TOC). All biologically active filters showed good performance relative to effluent turbidity levels, and headloss development. Preozonation of raw water increased AOC levels an average of 2.3 fold, and always increased filter effluent AOC levels relative to nonozonated water. Application of free chlorine to GAC filters did not inhibit biological activity. Application of chloramines to GAC filters showed a slight inhibitory affect relative to free chlorine. Effluent AOC levels averaged 82 µg/L at an EBCT of 5 min, and decreased to an average of 57 µg/L at 20 min EBCT. EBCT did affect TOC removals, with efficiencies averaging 29, 33, 42, and 51 % removal at EBCTs of 5, 10, 15 and 20 min, respectively. Trihalomethane formation potentials (THMFP) were related to TOC levels. Processes Chat decreased TOC levels also decreased THMFP. A preozonated GAC/sand filter (EBCT 10 min) achieved an annual average 54 % removal of THMFP precursors. Post disinfection of biologically treated effluents reduced HPC bacterial counts by 2-2.5log10. Post chlorination or chloramination of prechlorinated GAC/sand effluents resulted in a 20 %, or a 44 % (respectively) increase in AOC levels. Post disinfection of preozonated water resulted in small (<8%) AOC increases. Despite increases in AOC levels, prechlorinated water had lower AOC levels than preozonated water, even after post disinfection.